SnO2/Na-SnO2@MXene hybrid electrode materials for supercapacitor applications - Gautam, Nitin Kumar; Sharma, Aditya; Varshney, Mayora; Singh, Jitendra Pal; Shin, Hyun-Joon; Kumar, Shalendra; Brajpuriya, Ranjeet; Lee, Byeong hyeon; CHAE, KEUN HWA; Won, Sung Ok (Royal Society of Chemistry, 2025)
Correlations among the restacking tendency of MXenes' 2D layers, encapsulation of 2D MXenes with metal-oxide nanostructures, the effect of alkali metal loading, and electrochemical activities of MXenes are matters of debate and involve a deep understanding of their functionality and pseudocapacitive properties. Herein, MXene sheets were encapsulated with SnO2 and Na-SnO2 nanoparticles (NPs) and investigated for their structural, electronic, surface morphological, and electrochemical properties. X-ray diffraction (XRD) and transmission electron microscopy (TEM) results revealed the formation of MXenes and SnO2-based nanocomposite architectures. X-ray absorption spectroscopy (XAS) measurements, measured at the Sn M-edge and Ti L-edge, confirmed the presence of Sn4+ and Ti4+ ions in SnO2@MXene and/or Na-SnO2@MXene nanocomposites. A low concentration (similar to 1%) of Na loading in SnO2 NPs or SnO2@MXene nanocomposites facilitated supplementary redox features and, thus, offered nearly two times higher specific capacitance values than their bare counterparts. The log scan rate vs log peak current graphs unveiled a dominating surface-related charge storage mechanism in bare SnO2 NPs. Na loading enabled an appreciable diffusion-controlled charge storage mechanism, surface-related charge storage in the Na-SnO2@MXene nanocomposites, and a specific capacitance of 91.2 F g-1 at a scan rate of 5 mV s-1. The three-electrode cell of Na-SnO2@MXene nanocomposites exhibited similar to 89% retention for 3000 cycles. A two-electrode-based symmetric supercapacitor device, a Swagelok cell, was tested for the Na-SnO2@MXene sample with 1 M KOH electrolyte and 2 V LED. The symmetric supercapacitor offered a high energy density of similar to 75 W h kg-1 (at a power density of 7500 W kg-1) and a high-power density of 27 000 W kg-1 (at an energy density of 30 W h kg-1).